2003
DOI: 10.1046/j.1600-6135.2003.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Anemia: A Continuing Problem Following Kidney Transplantation

Abstract: Cardiovascular disease is a leading cause of death among kidney transplant recipients. Anemia, a risk factor for cardiovascular complications among patients with chronic kidney disease, has not been well characterized in kidney transplant recipients. We performed a retrospective cohort study of the prevalence of and factors associated with anemia among 240 patients who underwent kidney transplantation at our institution. The mean hematocrit (Hct) rose from 33% at 1 month after transplantation to 40% at 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
4
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 36 publications
10
119
4
5
Order By: Relevance
“…Immediately after transplantation, surgical blood loss, induction immunosuppression, frequent phlebotomy, and allograft dysfunction causing a persistent uremic state contribute to continued anemia (15). In patients with well-functioning allografts, anemia usually resolves by 3 to 6 months after transplantation (16). However, some patients have persistent anemia, and late PTA, defined as anemia occurring Ն6 to 12 months after transplantation, is common and understudied (11).…”
Section: Prevalencementioning
confidence: 99%
See 4 more Smart Citations
“…Immediately after transplantation, surgical blood loss, induction immunosuppression, frequent phlebotomy, and allograft dysfunction causing a persistent uremic state contribute to continued anemia (15). In patients with well-functioning allografts, anemia usually resolves by 3 to 6 months after transplantation (16). However, some patients have persistent anemia, and late PTA, defined as anemia occurring Ն6 to 12 months after transplantation, is common and understudied (11).…”
Section: Prevalencementioning
confidence: 99%
“…Mix et al (16) studied 240 kidney transplant recipients who were followed at an academic medical center in Boston and reported that 76% of patients had hematocrit Ͻ36% at the time of transplantation and 21% and 36% at 1 and 4 years after transplantation, respectively. Another study with 128 patients, using the WHO/ AST definition of anemia, reported the incidence of anemia as 26% at 5 years after transplantation (11).…”
Section: Prevalencementioning
confidence: 99%
See 3 more Smart Citations